Generals, colonels, and captains: Discourses of militarism, education, and learning in the Canadian university context - Taber, Nancy (Canadian Journal of Higher Education, 2014)
This article discusses a feminist discourse analysis that explores the ways in which discourses of learning interact with discourses of militarism at four Canadian civilian universities named for military leaders. I discuss how this particular research topic became apparent to me and explore the current national context where it can be argued that Canada is exchanging an identity of a peace-making country for one of war-making. I examine literature that connects education with militarism, taking a feminist anti-militarist approach, and discuss issues relating to academic freedom in critiquing one’s own institution. I explain my methodology and detail my findings, concluding that educators should continue to contest gendered militarism in higher education and society.